Pengaruh Sarana Prasarana Dan Media Pembelajaran Terhadap Proses Pembelajaran Siswa Stadi Kasus di MTs. Al-Musyarofah - Tarpin, Tarpin; Mukhlisin, Mukhlisin; Diani, Diani (Universitas Darunnajah Jakarta, Indonesia, 2022)
This study explains the influence of infrastructure and learning media on the learning process of students at Mts Al_Musyarofah. The research method used is a survey method through a quantitative approach. The population in this study were students of class VII MTs Al-Musyarrofah, totaling 50 students who were also used as research samples. The data collection technique uses a questionnaire. The data analysis technique used multiple linear regression coefficients. The results of this study indicate that there is no influence between Infrastructure (X1) on the student learning process (Y) as evidenced by ryx1 = 0.029 < r table 0.227 X1 has no effect on Y. While the Learning Media variable (X2) has an influence on the student learning process (Y) as evidenced by ryx2 0.735 > r table 0.227. There is a positive influence between infrastructure (X1) and learning media (X2) simultaneously (together) and significantly with the student learning process at MTs Al-Musyarrofah. It is proven by ryx1x2 0.600 > r table 0.227 and the coefficient of determination is 60% while the remaining 40% is influenced by other factors.